GREEN ENTREPRENEURSHIP: TRANSFORMING CHALLENGES INTO PROFITABLE SOLUTIONS - Wicaksono, Tutur (Universitas Bunda Mulia, 2025)
Green entrepreneurship serves as a vital link between environmental sustainability and economic profitability, providing innovative solutions to global issues like climate change and resource scarcity. This research investigates the dynamics of green ventures, emphasizing their capacity to convert environmental challenges into profitable opportunities. Utilizing the SALSA framework, a systematic literature review was conducted across prominent databases, identifying 120 relevant articles published between 2020 and 2025 on eco-innovation, financial performance, market trends, and regulatory impacts. The findings indicate that eco-innovation is a significant driver of success, with green entrepreneurs leveraging sustainable technologies, circular economy principles, and collaborative networks to address environmental issues while gaining a competitive edge. Contrary to the belief that sustainability-focused businesses are inherently unprofitable, the study demonstrates that green ventures often achieve financial success through long-term cost savings, premium pricing for eco-friendly products, and alignment with increasing consumer demand for sustainability. Regulatory frameworks, including subsidies, tax incentives, and environmental certifications, also play a crucial role in supporting green ventures by encouraging innovation and enabling market growth. These insights highlight the potential of green entrepreneurship as a viable approach to achieving both environmental and economic objectives. The study addresses a critical gap in the literature by integrating environmental and financial perspectives, offering actionable recommendations for policymakers, investors, and entrepreneurs to advance sustainable business practices and foster economic growth.